Necrotising hepatobacterium (NHPB) infection in penaeusvannamei with florfenicol and oxytetracycline: a comparative experimental study - Morales Covarrubias, María Soledad; Tlahuel Vargas, Lourdes; Martínez Rodríguez, Irma Eugenia; Lozano Olvera, Rodolfo; Palacios Arriaga, Juan Manuel (Revista Científica de la Facultad de Ciencias Veterinarias, 2012)
The present study is aimed to necrotising hepatobacterium (NHPB) infection, development in juvenile of Penaeus vannameiwith florfenicol (FF) (1.000g/kg biomass) and oxytetracycline (OTC) (6.070 g/kg biomass). HPLC analysis was used to confirm the antibiotics in food and samples, wet mount analysis, conventional histopathology, PCR and in situ hybridization were used to assess the prevalence, mortality and severity of NHP and to confirm NHPB infection. Wet-mount analysis and histopathological results demonstrated that the Penaeus vannamei fed with OTC had 100% NHPB prevalence disease severity index 1 (10%), 2 (28%), 3 (35%) and 4 (27%); meanwhile, P. vannamei fed with FF had 100% NHPB prevalence at disease severity index 1 (16%), 2 (36%), 3 (20%) and 4 (28%). The positive control had disease severity index 1 (10%), 2 (10%), 3 (80%) and 4 (0%); no disease NHP-B signs were revealed by the negative control. A weak positive signal was shown by the insitu hybridization from the 9th day, and a positive signal from the 15nd day. The results derived by the High-performance liquid chromatography (HPLC) analysis demonstrated that the maximum OTC level was in muscle (on the 6th and 7th day, respectively) and the FF level in hepatopancreas (HP), followed by muscle. It was conclude that FF and OTC used in medicated feed as an effective treatment in the control of NHPB disease in P. vannamei when the medication is supplied in disease severity index 1 and 2.